Six new species of Trichogramma Westwood (Hymenoptera: Trichogrammatidae) from a Brazilian forest reserve - Querino, R. B.; Zucchi, R. A. (Zootaxa, 2003)
An electrical suction trap set in a forest reserve in the State of São Paulo, Brazil, was used to collect Trichogramma species. Six new species were collected, namely Trichogramma acuminatum n. sp., Trichogramma alloeovirilia n. sp., Trichogramma parrai n. sp., Trichogramma pusillum n. sp., Trichogramma tupiense n. sp. and Trichogramma zucchii n. sp., which are being described herein.